Digital Technology and Consumer Purchase Decisions in Basic Necessities Purchases in Ogan Komering Ilir Regency - Gunarto, Muji; Putri, Erizia (Integrated Journal of Business and Economics (IJBE), 2025)
This study investigates the impact of digital technology utilization on consumer purchase decisions for necessities through the AISAS (Attention, Interest, Search, Action, Share) model, focusing specifically on users of the Ayo SRC application in Ogan Komering Ilir Regency, Indonesia. Despite the significant growth in the number of application users, there remain challenges in converting user Interest and Search activities into actual purchase Actions. Employing a quantitative associative approach, data were collected from 249 active application users and analyzed using Structural Equation Modeling based on Partial Least Squares (SEM-PLS). The findings revealed that digital technology significantly enhances consumer Attention, Interest, and Search behaviors. However, only the Attention stage significantly influenced actual Purchase Decisions. These results underline the critical role of creating attention-grabbing digital content to facilitate effective consumer conversion. The study offers theoretical insights into digital consumer behavior within the AISAS framework and practical recommendations for improving digital marketing strategies, particularly in optimizing consumer Attention to drive purchasing behaviors on digital platforms.